Determining the level of resources savings of the product life cycle - Komarysta, Bohdana; Bendiuh, Vladyslav (Lviv Politechnic Publishing House, 2017)
We proposed to use a useful life index to take into account the time of decay in the environment of the product and the time of useful product use. Application of a waste generation index to assess the level of waste generation at the stage of the product life cycle is suggested. The unitary index of efficient use of natural resources is calculated on the basis of thementioned indices.
Keywords: life cycle of the product; life cycle impact assessment; resource efficiency; index estimation